Chicken big - Graves, Keith (San Francisco : Chronicle Books, 2010)
A giant chicken hatches from an enormous egg, but the other chickens cannot accept that he is one of them.
Keywords: Chickens -- Fiction; Size -- Fiction; Humorous fiction